Analysis and Scientific Methodological Recommendations for Reducing the Delay on Railway Crossings - Tokhirov E. T. (Interactive science, 2021)
in this research focus on reduces waiting time and safe travel time at a level crossing. Current research interest is the application to improve implementation, reducing the waiting time for motor vehicles at a railroad crossing. At last, got at the level crossing 5% effective result for one improving period.
Keywords: железнодорожные переезды; задержка; автомобиль-машина; транспорт-инфраструктура; охраняемый ЛЦ; неохраняемый ЛЦ; level crossings; delay; vehicle-to-vehicle; vehicle-to-infrastructure; guarded LC; unguarded LC